Evaluating the Implementation of the Merdeka Curriculum in Elementary Schools: A CIPP Model Analysis of Literacy and Numeracy Learning - Tri Puji Lestari; Vina Iasha (International Journal of Education and Learning Studies, 2026)
This study evaluates the implementation of the Merdeka Curriculum in strengthening literacy and numeracy learning at an elementary school in Grobogan Regency, Indonesia. Despite the policy emphasis on flexible and student-centered learning, schools often face difficulties translating curriculum reforms into effective classroom practices. This study applies the CIPP (Context, Input, Process, Product) evaluation model integrated with the Taba curriculum development approach to analyze curriculum implementation and teacher practices. A qualitative case study design was used involving one school principal and six teachers at SD Negeri 7 Kuripan. Data were collected through semi-structured interviews, participatory classroom observations, and document analysis of curriculum and literacy programs. The data were analyzed using thematic analysis aligned with the CIPP framework and validated through data triangulation. The findings show the need to strengthen literacy–numeracy learning, improve instructional resources, support reflective teacher practices, and enhance the organization of school literacy programs. The study provides practical insights for improving curriculum implementation in elementary education.